OPTICAL SPECTROSCOPY OF CuAl ALLOYS UNDER ION BEAM SPUTTERING - M. Ait El Fqih; A. Kaddouri
Light emission during 5 keV Kr ion bombardment of CuAl alloys with different concentration is studied. The transient effect phenomenon has been investigated under two pressure conditions: one at base pressure (~10^-7 torr) and the other with introduction of oxygen gas (~10^-4 torr). The experimental oxygen sputtering yield was combined with simulation using the SRIM-code program. Both of them were in fairly good agreement.
Keywords: Physics; Optics